ANALYSIS OF SERVICES IN UZBEKISTAN REPUBLIC - Suyunov Asror Bakhtiyorovich (Antis Publisher, 2024)
In the article we analysis a development of digital economy in Uzbekistan. Trends and perspectives of economy in information and communication sphere of Uzbekistan. The volume of services provided by the main types of economic activity.